Collaborative Governance: Efforts to Re-functionalize the Youtefa Bay Women's Forest Area Based on Local Wisdom - Vince Tebay (Formosa Journal of Science and Technology, 2023)
The importance of governance collaboration as an effort to restore the function of the Youtefa Bay mangrove forest area which is not only as a disaster controller, but as a source of community life, managed from generation to generation with its local wisdom. The method used is library research. Where data comes from various literatures, by conducting text and discourse analysis. The results of this study indicate that the existence of mangrove forests on the coast of Youtefa Bay, Papua, is not only limited to disaster management, but is like a mother who gives life. Mangrove forests have become part of the community's customs. There is a division of territory to work; men earn a living at sea, and women are given mangrove forests as a local food source. Mangrove forests became a private space for women. Forest was later named "Women's Forest" in the local language called Tonotwiyat. Aside from being a source of food, it has become a tradition for women to be responsible for protecting and caring for the forest so that it remains sustainable. However, this tradition began to erode along with the times. Developments that are not environmentally friendly and waste that pollutes the forest are part of the fading of women's traditions of caring for the mangrove ecosystem. Rehabilitation of mangrove forest areas affected by development is one of the efforts made by the government. Efforts to preserve mangrove forest areas are not only the task of the government. However, it must be carried out collaboratively with the government, community, NGOs, and the private sector. The collaborative governance approach as an effort to restore the function of mangrove forests can be carried out by prioritizing the local wisdom values ​​of the community. This collaboration is here to answer the lack of resources of each actor.